2014
DOI: 10.1124/dmd.113.056689
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Human OCT1, OCT3, and CYP3A4 to Nitidine Chloride–Induced Hepatocellular Toxicity

Abstract: Nitidine chloride (NC), a quaternary ammonium alkaloid, has numerous pharmacological effects, such as anticancer activity. However, it was found that NC also has hepatocellular toxicity. Because organic cation transporters 1 and 3 (OCT1 and OCT3) might mediate the influx of NC into hepatocytes, multidrug and toxin extrusion 1 (MATE1) probably mediates the efflux of NC from hepatocytes, while cytochrome P450 (P450) enzymes might contribute to NC metabolism, the present study was to evaluate the contribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Interestingly, NC was found to be a candidate substrate of OCT1 and OCT3 that transfer NC into hepatocytes. Moreover, MATE1 makes NC leave from hepatocytes, while CYPs contributed to NC metabolism such as CYP3A4 and attenuated the hepatic toxicity of NC [23]. TOP1 and TOP2A are key tumor drivers in liver cancer [24], suggesting that TOP1 and TOP2A might be promising targets for treating malignances [25].…”
Section: Liver Cancermentioning
confidence: 99%
“…Interestingly, NC was found to be a candidate substrate of OCT1 and OCT3 that transfer NC into hepatocytes. Moreover, MATE1 makes NC leave from hepatocytes, while CYPs contributed to NC metabolism such as CYP3A4 and attenuated the hepatic toxicity of NC [23]. TOP1 and TOP2A are key tumor drivers in liver cancer [24], suggesting that TOP1 and TOP2A might be promising targets for treating malignances [25].…”
Section: Liver Cancermentioning
confidence: 99%
“…Li et al . suggested that NTD is metabolized by hepatic enzymes such as P450, which mainly catalyzes the oxidation of drugs and, therefore, concluded that the oral bioavailability of NTD is probably very low . In the present study, however, oral NTD concentrate significantly inhibited tumor growth (Fig.…”
Section: Discussionmentioning
confidence: 44%
“…In addition, human multidrug and toxin extrusion 1 (hMATE1), an H + ‐coupled organic cation exporter, is also expressed in the brush border membrane of proximal tubule cells (Omote et al, ; Kusuhara and Sugiyama, ). Because NC was also identified as a substrate of hMATE1 in our previous study (Li et al, ), MATE1 might mediate the efflux of NC from renal tubular epithelial cells and alleviate NC‐induced nephrotoxicity.…”
Section: Introductionmentioning
confidence: 82%
“…The concentrations of MPP + and NC in the cellular uptake and tissue samples were determined by the modified LC–MS/MS method (Li et al, ) using an Agilent 1290/6460 LC–MS with a triple quadrupole mass spectrometer. Two or eight volumes of acetonitrile containing 90 ng mL ‐1 loratadine as an internal standard (IS) were added to the cell lysates or tissue samples, respectively, to precipitate proteins.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation